Development of a Procedural Guide to Implement Response to Intervention (RtI) With High-Ability Learners. Issue 1 (2nd January 2016) - Robertson, Stephanie; Pfeiffer, Steven
Abstract : In recent years, a focus on individual student needs has set the stage for tailoring educational interventions to address issues of students who are not working up to educational proficiency standards outlined in the No Child Left Behind (NCLB) legislation. This new pedagogical model may provide a unique opportunity to meet the needs of high-ability students who are not working to their potential in the classroom. Research indicates that gifted students allowed to work on material beyond the common core curriculum instead of merely maintaining the pace of the rest of the class actually perform better on end-of-the-year testing in math and science than gifted controls who did not pursue additional work. Bright students, like all students, demonstrate increased motivation and classroom performance when provided with academic material that appropriately challenges them. Response to intervention (RtI) establishes differentiated curriculum as the standard in America's schools. It holds promise for all students, not only students who are lagging behind. RtI addresses student underperformance, whether due to a lack of motivation, boredom, or any number of potential factors moderating the learning of high-ability students as well as the average learner. This article reports on a study that developed and field tested a procedural guide for implementation of the RtI model with gifted students.